2021
DOI: 10.1097/ede.0000000000001443
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Self-reported Opioid Agonist Treatment Among People Who Inject Drugs Using Prescription Dispensation Records

Abstract: The results reported herein correspond to specific aims of a Fredrick Banting and Charles Best Canada Graduate Scholarship-Doctoral Award to Zachary Bouck from the Canadian Institutes of Health Research (CIHR). This study was supported by ICES, which is funded by an annual grant from the Ontario Ministry of Health and Long-Term Care. During the study, salary support was received via Tier 2 Canada Research Chair awards to Dr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…For example, over 90% of participants reported recent homelessness or unstable housing at baseline ( Scheim, Sniderman, et al, 2021 ), a structural vulnerability that has been previously associated with difficulty accessing OAT ( Prangnell et al, 2016 ). Third, OiSIS-Toronto participants are asked at baseline for additional consent to having their questionnaire data transferred and linked at ICES—a non-profit research institute authorized under Ontario's health information privacy law to collect and analyze health care and demographic data for health system evaluation and improvement ( Bouck et al, 2022 ; Scheim, Sniderman, et al, 2021 ). The linkage process has been summarized previously in greater detail ( Bouck et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, over 90% of participants reported recent homelessness or unstable housing at baseline ( Scheim, Sniderman, et al, 2021 ), a structural vulnerability that has been previously associated with difficulty accessing OAT ( Prangnell et al, 2016 ). Third, OiSIS-Toronto participants are asked at baseline for additional consent to having their questionnaire data transferred and linked at ICES—a non-profit research institute authorized under Ontario's health information privacy law to collect and analyze health care and demographic data for health system evaluation and improvement ( Bouck et al, 2022 ; Scheim, Sniderman, et al, 2021 ). The linkage process has been summarized previously in greater detail ( Bouck et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Third, OiSIS-Toronto participants are asked at baseline for additional consent to having their questionnaire data transferred and linked at ICES—a non-profit research institute authorized under Ontario's health information privacy law to collect and analyze health care and demographic data for health system evaluation and improvement ( Bouck et al, 2022 ; Scheim, Sniderman, et al, 2021 ). The linkage process has been summarized previously in greater detail ( Bouck et al, 2022 ). Briefly, 74% (521/701) of OiSIS-Toronto participants recruited by March 19 th , 2020, consented to and were successfully linked at ICES.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, research has shown both the reliability and validity of self-reported data among people who use drugs. 55 , 56 Nonetheless, future research is needed, including mixed-methods approaches to confirm outcomes of safer supply programs.…”
Section: Discussionmentioning
confidence: 99%